The yeast GAL11 protein binds to the transcription factor IIE through GAL11 regions essential for its in vivo function. - Sakurai, H (1996)
The GAL11 gene encodes an auxiliary transcription factor required for full expression of many genes in yeast. The GAL11-encoded protein (Gal11p) has recently been shown to copurify with the holoenzyme of RNA polymerase II. Here we report that Gal11p stimulates basal transcription in a reconstituted transcription system composed of recombinant or highly purified transcription factors, TFIIB, TFIIE, TFIIF, TFIIH, and TATA box-binding protein and core RNA polymerase II. We further demonstrate that each of the two domains of Gal11p essential for in vivo function respectively participates in the binding to the small and large subunits of TFIIE. The largest subunit of RNA polymerase II was coprecipitated by anti-hemagglutinin epitope antibody from crude extract of GAL11 wild type yeast expressing hemagglutinintagged small subunit of TFIIE. Such a coprecipitation of the RNA polymerase subunit was seen but in a greatly reduced amount, if extract was prepared from gal11 null yeast. In light of these findings, we suggest that Gal11p stimulates promoter activity by enhancing an association of TFIIE with the preinitiation complex in the cell.